الثقافة التنظيميّة لدى العاملين بأكاديمية الدراسات العليا/ مصراتة وعلاقتها بالأداء الوظيفي (Journal of Academic Research, 2021)
This research aims to determine the level of organizational culture among the employees of the Academy of Graduate Studies / Misurata and its relationship to job performance. To achieve this objective, the descriptive analytical approach was used. The required data was collected using the questionnaire tool. The questionnaire consists of two main axes: (organizational culture) with three elements, and (performance) axis. The research sample consists of (22) respondents, who were randomly selected through the stratified method. Respondents are administrators  of the Academy of Graduate Studies in Misurata. They represent 40% of the research community of approximately (57) employees. The analysis of the data was quantitative through the SPSS21 statistical program. It aims to achieve the following: Knowing the level of organizational culture prevailing among the employees of the Academy of Graduate Studies / Misurata. It also aims to realize the level of efficiency of their job performance, as well as determining the relationship or the degree of influence of organizational culture on job performance within the concerned academy. in addition, it aims to explore the extent to which there are statistically significant differences in the degree of influence of the prevailing organizational culture on the job performance of the Academy's employees which might be attributed to the variables "Educational Qualification" and "Years of Experience.The most prominent results of this research were the following: The level of the prevailing organizational culture among employees of the Academy of Graduate Studies / Misurata was medium. In addition, the level of efficiency of job performance among employees of the Academy of Graduate Studies / Misurata was medium as well. Moreover, the results of the study show that there is a strong direct relationship between the prevailing organizational culture and job performance, as the stronger the organizational culture, the more efficient the administrative performance is. while there are no statistically significant differences in the degree of influence of the prevailing organizational culture on the job performance of the Academy's employees, which could be attributed to the variables of "educational qualification" and "years of experience."